New Challenges in Corporate Governance: Theory and Practice 2019
DOI: 10.22495/ncpr_52
|View full text |Cite
|
Sign up to set email alerts
|

The link between CSR and the board’s role: A theoretical framework on non-financial disclosure

Abstract: This study aims to review the main organisational theories identifying the significant roles of the board of directors in order to analyse how the board composition influences both CSR activity and disclosure. We present a literature review of the main organisational theories in order to identify their implications for non-financial information disclosure and disclosure of diversity information. The non-financial information is a tool for organisations to discharge their accountability to various stakeholder g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…From the agency theory perspective, corporate disclosure is used to harmonize the interests of managers and shareholders (Khaireddine et al, 2020). Agency theory suggests that the monitoring role of boards influence firms to disclose sustainability information in capital markets to reduce agency costs and information asymmetry between managers and shareholders (Quattrociocchi, Mercuri, & Sergiacomi, 2019). Galbreath (2011) finds that boards that have a strong complement of gender diversity are expected to offer more effective monitoring of agents, as well as lead to stronger enforcement of ethical conduct.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…From the agency theory perspective, corporate disclosure is used to harmonize the interests of managers and shareholders (Khaireddine et al, 2020). Agency theory suggests that the monitoring role of boards influence firms to disclose sustainability information in capital markets to reduce agency costs and information asymmetry between managers and shareholders (Quattrociocchi, Mercuri, & Sergiacomi, 2019). Galbreath (2011) finds that boards that have a strong complement of gender diversity are expected to offer more effective monitoring of agents, as well as lead to stronger enforcement of ethical conduct.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The board is the main vehicle through which corporate governance occurs. Therefore, it is responsible for protecting the interests of the stakeholders (Quattrociocchi, Mercuri & Sergiacomi, 2019) and for the company's accountability and transparency through information disclosure (Dias, Rodrigues & Russell, 2017). Board composition is a determinant factor for Corporate and Social Responsibility (CSR) disclosure, as it is influenced by the choices, motives and values of those involved in the decision-making process (Khan, Muttakin & Siddiqui, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…BoD is the mean by which a company protects not only the shareholders' interest but stakeholder interest as well (Pérez Carrillo et al, 2007;Quattrociocchi et al, 2019). BoD's main responsibility is to serve the link between shareholders and corporate managers and its supervisory capacity is determined by the size of BoD and the board composition (Villanueva-Villar et al, 2016).…”
Section: Board Of Directorsmentioning
confidence: 99%
“…The quality of CSR disclosure is important to pay attention to in order to control social and environmental risks (Gray, 2001;Quattrociocchi et al, 2019;Wu & Hu, 2019) and produce relevant information for stakeholders. However, in research conducted by Anugerah, Saraswati, Andayani (2018) using a quality measurement framework made by Michelon, Pilonato, & Ricceri (2015) as a tool to measure the quality of CSR disclosure in the Indonesian state, different assumptions were found that state voluntary practices from the stand alone report, assurance and reporting guidelines do not improve the quality of disclosure.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%